Professional bags prestigious award. - The, Star (The Star, 2014)
AeU is an international institution that offers quality education and flexible academic programmes for professional and working adults. "Kumaresan Muthusamy is confident that AeU MBA graduates have an eager over others as they are equipped with the necessary skills to succeed in a highly competitive working environment".